Self-medication practices in riverside communities in the Brazilian Amazon Rainforest - Abel Santiago Muri Gama; Silvia Regina Secoli
ABSTRACT Objectives: to analyze the practice of self-medication and the associated factors in the riverside population of the Middle Solimões river region - Amazon rainforest. Methods: a cross-sectional population-based study conducted between April and July 2015, through interviews at home. Results: the prevalence of self-medication among the riverside population was 76.3%. Analgesics and antibacterials were the main therapeutic classes used in self-medication. Self-medication proved to be associated with the male gender, young people, not having sought the health service in the last month, longer commuting from the community to the urban area and the habit of consuming allopathic medicines on their own. Conclusions: self-medication among the riverside population of Coari - Amazon may reflect the need to seek self-care by people, with the use of allopathic medicines without prescription, mainly due to the restricted access to health services.